Enhancing Engagement: Effective Strategies for EFL Teachers in Online Classes during the Pandemic Era - Andi Irlina; Hidayah Nor; Akhmad Zaini (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2023)
In online learning, teachers use a number of support strategies to engage learners. The right strategies at the right time  make distance learning effective and keep students engaged. The purpose of the research is to find out the strategies that teachers use to maintain performance in English language learners during the pandemic, and to find  the most appropriate strategy that teachers use to maintain performance in English language courses during the pandemic. The researchers used descriptive qualitative research to examine the  strategies of teachers in online English lessons in this study. It explains the teaching strategies used in MTs Negeri 1 Banjarmasin and the participants were three English teachers which teach on VII A, VII B, and VII C. The researchers uses two techniques to collect data. There are observations and interviews. Observations were made in Online Class VII (A, B and C)  MTs Negeri 1 Banjarmasin. The interview was then conducted face-to-face with three English teachers. The results showed that the teacher's strategy in teaching  VII grade students (A, B and C), the researchers concluded that  six active learning strategies were used in the online learning of the three participating teachers. Learning strategies include discussion, problem solving, brainstorming, peer teaching, case studies and discussions. The researchers also found that  three teachers preferred to use the conversational strategy because that strategy is very easy for teachers to implement, especially in class VII, where that strategy has become the most suitable strategy for teaching English in online learning.